Guidelines from an expert panel for the management of diabetic macular edema in the Malaysian population - Md Saleh, Rafidah; Wong, Hon Seng; Mohd Jamil, Nurfahzura; Ngah, Nor Fariza; Muhamad, Nor Asiah (Press of International Journal of Ophthalmology, 2023)
AIM: To derive a Malaysia guideline and consensus as part of the Malaysia Retina Group’s efforts for diagnosis, treatment, and best practices of diabetic macular edema (DME). The experts’ panel suggests that the treatment algorithm to be divided into groups according to involvement the central macula. The purpose of DME therapy is to improve edema and achieve the best visual results with the least amount of treatment load. METHODS: On two different occasions, a panel of 14 retinal specialists from Malaysia, together with an external expert, responded to a questionnaire on management of DME. A consensus was sought by voting after compiling, analyzing and discussion on first-phase replies on the round table discussion. A recommendation was deemed to have attained consensus when 12 out of the 14 panellists (85%) agreed with it. RESULTS: The terms target response, adequate response, nonresponse, and inadequate response were developed when the DME patients’ treatment responses were first characterized. The panelists reached agreement on a number of DME treatment-related issues, including the need to classify patients prior to treatment, first-line treatment options, the right time to switch between treatment modalities, and side effects associated with steroids. From this agreement, recommendations were derived and a treatment algorithm was created. CONCLUSION: A detail and comprehensive treatment algorithm by Malaysia Retina Group for the Malaysian population provides guidance for treatment allocation of patients with DME.